Implications of mechanical circulatory support devices in a pregnant woman with cardiogenic shock - Johanna A. van der Zande; Dalila Blel; Robert M. Kauling; H. Rob Taal; Jeroen J. H. Bunge; Attie Go; Henrik Endeman; Arie Franx; Jerome M. J. Cornette (Exploration of Cardiology, 2025)
Data on the use of mechanical circulatory support devices in pregnant women are limited. A 27-year-old woman at 27 weeks and 6 days of gestation was supported by three different mechanical circulatory support devices due to cardiogenic shock. She came into spontaneous labor, which was complicated by major hemorrhage at the cannulation site, fetal distress, and transverse position, requiring emergency cesarean section. The postpartum period was complicated by intra-abdominal bleeding and arterial occlusion of lower extremity. When using mechanical circulatory support devices in pregnant women, a multidisciplinary approach is recommended.